Functional genomics and gene-environment interaction highlight the complexity of congenital heart disease caused by Notch pathway variants. (9th December 2019) - Chapman, Gavin; Moreau, Julie L M; I P, Eddie; Szot, Justin O; Iyer, Kavitha R; Shi, Hongjun; Yam, Michelle X; O'Reilly, Victoria C; Enriquez, Annabelle; Greasby, Joelene A; Alankarage, Dimuthu; Martin, Ella M M A; et al.
Abstract: Congenital heart disease (CHD) is the most common birth defect and brings with it significant mortality and morbidity. The application of exome and genome sequencing has greatly improved the rate of genetic diagnosis for CHD but the cause in the majority of cases remains uncertain. It is clear that genetics, as well as environmental influences, play roles in the aetiology of CHD. Here we address both these aspects of causation with respect to the Notch signalling pathway. In our CHD cohort, variants in core Notch pathway genes account for 20% of those that cause disease, a rate that did not increase with the inclusion of genes of the broader Notch pathway and its regulators. This is reinforced by case-control burden analysis where variants in Notch pathway genes are enriched in CHD patients. This enrichment is due to variation in NOTCH1 . Functional analysis of some novel missense NOTCH1 and DLL4 variants in cultured cells demonstrate reduced signalling activity, allowing variant reclassification. Although loss-of-function variants in DLL4 are known to cause Adams-Oliver syndrome, this is the first report of a hypomorphic DLL4 allele as a cause of isolated CHD. Finally, we demonstrate a gene-environment interaction in mouse embryos between Notch1 heterozygosity and low oxygen- or anti-arrhythmic drug-induced gestational hypoxia, resulting in an increased incidence of heart defects. This implies that exposure to environmental insults such as hypoxia could explain variable expressivity and penetrance of observed CHD in families carrying Notch pathway variants.